Analysis of the relationship between the autonomy of Turkish elderly people and their happiness and anxiety-depression status: a cross-sectional study - Tastan, Sevinc; Ayhan, Hatice; Kose, Gulsah; Iyigun, Emine; Gokcul, Seray (Elsevier, 2019)
[Abstract Not Available]